A new model of growth restriction factor for hypoeutectic aluminium alloys. (1st April 2020) - Zhang, Lili; Jiang, Hongxiang; He, Jie; Zhao, Jiuzhou
Abstract: A model is proposed to calculate growth restriction factor Q new for hypoeutectic aluminium alloy by considering not only the liquidus slope, solute concentration and partition coefficient, but also the solute solubility in α-Al and eutectic composition. The relation between α-Al average grain size and Q new is checked. The results demonstrate that different from the previous growth restriction factor which monotonically depends on the solute concentration c 0, Q new increases first with c 0 up to solute solubility in α-Al and then decreases with c 0 . Grain size increases with the inverse square root of Q new over the whole range of the hypoeutectic compositions. Graphical abstract: Image, graphical abstract